Moral values, social ideologies and threat-based cognition: Implications for intergroup relations - Morris, David S. M.; Stewart, Brandon D. (Frontiers in Psychology, 2022)
Moral Foundations Theory (MFT) has provided an account of the moral values which underscore different cultural and political ideologies, these moral values of harm, fairness, loyalty, authority, and purity can help to explain differences in political and cultural ideologies; however, the extent to which moral foundations relate to strong social ideologies, intergroup processes and threat perceptions is still underdeveloped. To explore this relationship, we conducted two studies. In Study 1 (N = 157), we considered how the moral foundations predicted strong social ideologies such as authoritarianism (RWA) and social dominance orientation (SDO) as well as attitudes toward immigrants. Here we demonstrated that more endorsement of individualizing moral foundations (average of harm and fairness) was related to less negative intergroup attitudes, which was mediated by SDO, and that more endorsement of binding moral foundations (the average of loyalty, authority, and purity) was related to more negative attitudes, which was mediated by RWA. Crucially, further analyses also suggested the importance of threat perceptions as an underlying explanatory variable. Study 2 (N = 388) replicated these findings and extended them by measuring attitudes toward a different group reflecting an ethnic minority in the U.S, and by testing the ordering of variables while also replicating and confirming the threat effects. These studies have important implications for using MFT to understand strong ideologies, intergroup relations and threat perceptions.